Diagnostic And Analysis Misconceptions In Learning Redox And Electrochemistry Topic In Chemistry Students - Lubis, Ervi Luthfi Sheila (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The research’s objective to know students misconceptions on redox and electrochemistry concept, the sources of students misconceptions, to avoid misconception by students worksheet. involved 30 students was studied general chemistry in chemistry department, Islamic State University of Syekh Ali Hasan Ahmad Addary Padangsidimpuan. Instrument of the research is diagnostic test with three tier question to know misconceptions on students, interview sheet to know sources of misconceptions. The result of research are (1) It was founded that students had misconceptions on redox and electrochemistry concept with percentage 52.6% .(2) It was founded 3 sources that affect students misconceptions on redox and electrochemistry, that are Students, have wrong interpreted from books and teacher, Internet that has many unbelievable sources, Friends that have wrong concept and sharing to other students.